Análise do comportamento e (cor)relações de propriedades térmicas, físicas, químicas e morfológicas de solos no semiárido brasileiro - Costa, Juliana Rayssa Silva (2022)
Soil is a natural resource that varies over time and space, has diverse chemical, physical and biological characteristics, and performs numerous socioenvironmental functions, which together with vegetation and the atmosphere live in constant interaction and change. Given this situation, in the present work we analyzed the thermal, physical, chemical and morphological behavior and the (color)relationship between these in the surface layer of soils located in Cariri Paraibano, a Brazilian semiarid region. For this, 10 soil samples were collected in 10 municipalities (Cabaceiras, Serra Branca, Coxixola, Caraúbas, Congo, Camalaú, São João do Tigre, São Sebastião do Umbuzeiro, Monteiro and Ouro Velho) and thermal properties of these were obtained (diffusivity, conductivity, thermal resistance, heat capacity and temperature) through the Properties Analyzer - KD2 Pro; carrying out uncertainty treatment using Normal Distribution and descriptive statistics of soil thermal parameters; tabulation and descriptive statistics were also made of physical (texture) and chemical parameters (pH; potential acidity, exchangeable cations - A13+, Ca2+, Mg2+, K+, Na+; P; P-rem; ISNa; MO; sum of bases; capacity of effective cation exchange; total cation exchange capacity; saturation by bases) and morphological (gravel; color; structure - degree, size and type; consistency; roots; pores and transition) to correlate them to thermal properties through Correlation of Pearson and significance test of these results using the t Test. Based on the results obtained, it was shown that the diffusivity and thermal conductivity of the soils evaluated are generally low, causing the temperature to be high and greater variability on the surface, with a small depth of heat penetration and less heat storage. Diffusivity, conductivity and heat capacity correlated only with morphological properties (structure - degree and size, consistency, number of pores, gravel and plasticity); thermal resistance was related to chemical and morphological aspects (P- rem and degree - weak and moderate) and temperature with physical (fine sand and silt), chemical (M and MO) and morphological aspects (structure - moderate degree and size very small, small and medium, consistency - dry and soft and number of pores - common). In view of the above, correlations not previously presented in soil studies in Brazil were verified; the hypothesis of this thesis was proven that in addition to organic matter, physical, chemical and morphological characteristics together influence the thermal properties of the soils present, exposing exactly what the specific variables are for this; and the physical quality of soils would be shaped by the structure, porosity, consistency and dynamics of soil moisture.